Assessing anaerobic gut fungal diversity in herbivores using D1/D2 large ribosomal subunit sequencing and multi‐year isolation. (11th August 2020) - Hanafy, Radwa A.; Johnson, Britny; Youssef, Noha H.; Elshahed, Mostafa S.
Summary: The anaerobic gut fungi (AGF, Neocallimastigomycota) reside in the alimentary tracts of herbivores where they play a central role in the breakdown of plant material. Here, we report on the development of the hypervariable domains D1/D2 of the large ribosomal subunit (D1/D2 LSU) as a barcoding marker for the AGF. We generated a reference D1/D2 LSU database for all cultured AGF genera, as well as the majority of candidate genera encountered in prior internal transcribed spacer 1 (ITS1)‐based surveys. Subsequently, a D1/D2 LSU‐based diversity survey using long read PacBio SMRT sequencing was conducted on faecal samples from 21 wild and domesticated herbivores. Twenty‐eight genera and candidate genera were identified, including multiple novel lineages that were predominantly, but not exclusively, identified in wild herbivores. Association between certain AGF genera and animal lifestyles, or animal host family was observed. Finally, to address the current paucity of AGF isolates, concurrent isolation efforts utilizing multiple approaches to maximize recovery yielded 216 isolates belonging to 12 different genera, several of which have no prior cultured‐representatives. Our results establish the utility of D1/D2 LSU and PacBio sequencing for AGF diversity surveys, the culturability of multiple AGF taxa, and demonstrate that wild herbivores represent a yet‐untapped reservoir of AGF diversity.